2012
DOI: 10.1002/cbic.201100601
|View full text |Cite
|
Sign up to set email alerts
|

UV Radiation Induces Genome‐Mediated, Site‐Specific Cleavage in Viral Proteins

Abstract: Much research has been dedicated to understanding the molecular basis of UV damage to biomolecules, yet many questions remain regarding the specific pathways involved. Here we describe a genome‐mediated mechanism that causes site‐specific virus protein cleavage upon UV irradiation. Bacteriophage MS2 was disinfected with 254 nm UV, and protein damage was characterized with ESI‐ and MALDI‐based FT‐ICR, Orbitrap, and TOF mass spectroscopy. Top‐down mass spectrometry of the products identified the backbone cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
(28 reference statements)
2
35
0
Order By: Relevance
“…3 and statistical analyses, it is apparent that damage to the nucleic acid is the primary cause of the loss of viral infectivity across the germicidal UV spectrum. Although UV light causes photoproducts or structural modifications in capsid proteins (21), and genome-mediated protein damage has been demonstrated in MS2 (30), this damage does not appear to contribute significantly to a loss of MS2 viral infectivity. In contrast, the spectral sensitivity of adenovirus diverged from the sensitivity of its genome at wavelengths below 240 nm, suggesting that nongenomic damage contributes to UV inactivation at these wavelengths (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and statistical analyses, it is apparent that damage to the nucleic acid is the primary cause of the loss of viral infectivity across the germicidal UV spectrum. Although UV light causes photoproducts or structural modifications in capsid proteins (21), and genome-mediated protein damage has been demonstrated in MS2 (30), this damage does not appear to contribute significantly to a loss of MS2 viral infectivity. In contrast, the spectral sensitivity of adenovirus diverged from the sensitivity of its genome at wavelengths below 240 nm, suggesting that nongenomic damage contributes to UV inactivation at these wavelengths (28).…”
Section: Resultsmentioning
confidence: 99%
“…One explanation as to why there would still be genomic damage from irradiation at wavelengths below 240 nm is the potential for proteins absorbing UV at these wavelengths to transfer energy or extend damage to the RNA. Wigginton et al (30) showed that the presence of viral RNA contributed to site-specific protein damage, suggesting an energy transfer from RNA to viral proteins in MS2 following UV radiation at 253.7 nm. At wavelengths below 240 nm, where protein absorption of UV is highest, it is plausible that the energy transfer would occur in the opposite direction; energy preferentially absorbed by proteins could be generating site-specific RNA damage, resulting in a loss of viral infectivity.…”
Section: Resultsmentioning
confidence: 99%
“…7). In previous work (37), it was shown that the degradation of peptide 44 -49 in MS2 was caused by backbone cleavage around amino acids Cys46 and Ser47. This cleavage event was facilitated by the presence of both RNA and cysteine at the cleavage site.…”
Section: Discussionmentioning
confidence: 99%
“…These amino acids are responsible for CAR host binding in the fiber knob of HAdV (50). In particular, tyrosine is susceptible to oxidation and degradation by light (25). Thus, indirect solar disinfection may hamper host binding and lower the infectivity of HAdV-2.…”
Section: Mechanisms Contributing To Solar Disinfection Of Adenovirusmentioning
confidence: 99%
“…Susceptible amino acids and peptides located in these structures may play an important role in adenovirus inactivation processes during irradiation with sunlight and UV light. Tyrosine, histidine, and lysine in the fiber head are crucial for host binding in adenovirus (24), and in particular, tyrosine is susceptible to degradation by light (25). Finally, the efficiency of adenovirus inactivation in a setting representative of solar disinfection of drinking water (SODIS), hence exposed to sunlight in a polyethylene terephthalate (PET) bottle, was investigated.…”
mentioning
confidence: 99%